Analytical simulation of Darcy-Forchheimer nanofluid flow over a curved expanding permeable surface - Rehman A.; Al-Buriahi M.S.; Ali H.E.; Jan R.; Khan I.A. (Institute of Physics, 2025)
This research paper presents an analytical simulation of Darcy-Forchheimer flow over a porous curve stretching surface. In fluid dynamics, the Darcy-Forchheimer model combines Forchheimer adjustment and high-velocity effects with Darcy?s formula for porous media flow: two nanofluid particles, molybdenum disulphide, and graphene oxide, form nanofluid with the base fluid blood. The governing partial differential equations for momentum and energy are converted into a nonlinear ordinary differential equations system by applying the appropriate similarity transformations. The homotopy analysis method is used to solve the transform equations analytically. The impact of essential factors includes the Forchheimer parameter, porosity parameter, slip parameter, Eckert number, nanoparticle volume friction, magnetic field parameter, and curvature parameter. The results have applications in the design of sophisticated cooling systems, where effective thermal control is essential. ? 2024 The Japan Society of Fluid Mechanics and IOP Publishing Ltd. All rights, including for text and data mining, AI training, and similar technologies, are reserved.